2010
DOI: 10.1208/s12249-010-9564-z
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Matrix as Oral Drug Delivery Vehicle for Colon Cancer Treatment

Abstract: Abstract. Colon cancer is the fourth most common cancer globally with 639,000 deaths reported annually. Typical chemotherapy is provided by injection route to reduce tumor growth and metastasis. Recent research investigates the oral delivery profiles of chemotherapeutic agents. In comparison to injection, oral administration of drugs in the form of a colon-specific delivery system is expected to increase drug bioavailability at target site, reduce drug dose and systemic adverse effects. Pectin is suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 85 publications
1
81
0
1
Order By: Relevance
“…Pectin is one of the most extensively studied natural polysaccharides due to its suitability for colon-specific drug delivery (Liu et al, 2007;Sriamornsak, 2011;Wong et al, 2011;Mamani Crispin et al, 2012). However, pectin's colon-specificity is compromised by its high solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Pectin is one of the most extensively studied natural polysaccharides due to its suitability for colon-specific drug delivery (Liu et al, 2007;Sriamornsak, 2011;Wong et al, 2011;Mamani Crispin et al, 2012). However, pectin's colon-specificity is compromised by its high solubility.…”
Section: Introductionmentioning
confidence: 99%
“…It is the third most common cancer and the fourth leading cause of mortality among cancer patients (Jemal et al, 2010). Surgery with adjunctive chemotherapy and/or radiotherapy is considered the gold standard treatment for colon cancer (Wong et al, 2011). However, nearly 40% of surgical patients develop recurrence or metastases and chemotherapy often has adverse effects and off-target actions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have shown that Ca-pectinate beads are less sensitive to ions and chemical agents that destabilize Ca-alginate beads [2,4]. In order to enhance the stability of the beads in bioprocess applications, their mechanical strength should be improved, which in turn is influenced by their size and shape [7]. Therefore, it is important to have a bead formation system that is capable of forming mono-dispersed and spherical beads.…”
Section: Introductionmentioning
confidence: 99%